New horizons of biomaterials in treatment of nerve damage in diabetes mellitus: A translational prospective review - Raghav, Alok; Singh, Manish; Jeong, Goo-Bo; Giri, Richa; Agarwal, Saurabh; Kala, Sanjay (Frontiers in Endocrinology, 2022)
Background Peripheral nerve injury is a serious concern that leads to loss of neuronal communication that impairs the quality of life and, in adverse conditions, causes permanent disability. The limited availability of autografts with associated demerits shifts the paradigm of researchers to use biomaterials as an alternative treatment approach to recover nerve damage. Purpose The purpose of this study is to explore the role of biomaterials in translational treatment approaches in diabetic neuropathy. Study design The present study is a prospective review study. Methods Published literature on the role of biomaterials in therapeutics was searched for. Results Biomaterials can be implemented with desired characteristics to overcome the problem of nerve regeneration. Biomaterials can be further exploited in the treatment of nerve damage especially associated with PDN. These can be modified, customized, and engineered as scaffolds with the potential of mimicking the extracellular matrix of nerve tissue along with axonal regeneration. Due to their beneficial biological deeds, they can expedite tissue repair and serve as carriers of cellular and pharmacological treatments. Therefore, the emerging research area of biomaterials-mediated treatment of nerve damage provides opportunities to explore them as translational biomedical treatment approaches. Conclusions Pre-clinical and clinical trials in this direction are needed to establish the effective role of several biomaterials in the treatment of other human diseases.